EFFECT OF VERMICOMPOSTING, NITROGEN FERTILIZATION AND INOCULATION WITH Rhizobium phaseoli IN COMMON BEAN (Revista de Ciências Agroveterinárias, 2005)
Two experiments were conducted under field conditions in a Hapludol Lhitic soil. The aim was to evaluate the vermicomposting utilization with inoculation of the seeds with Rhizobium phaseoli and the side-dress of nitrogen fertilization in common bean production. The experimental design was a randomized complete block, with four repetitions. In the growing season of 2000/2001 there was no significant difference among the fertilization forms for plant dry mass, number of nodules per plant and grain production. The inoculation with Rhizobium phaseoli increased plant dry mass and the number of legumes per plant. The use of side-dress nitrogen fertilization presented similar results, and also increased in the grain production. In the growing season of 2001/2002, there were similar results among the different forms of base fertilization, demonstrating that organic fertilization could be as important as mineral fertilization to common bean grain yield. There were higher differences in the mycorrhizal association in 2000/2001, but such differences tend to decrease when common bean is grown in the same area for several years.
Keywords: Organic fertilization; biological fixation of nitrogen; mycorrhizal association; nutrition.